Phononic Weyl Nodal Lines and Weyl Pairs in van der Waals Heavy Fermion Material CeSiI - Li, Fulei; Yu, Tianye; Lai, Junwen; Liu, Jiaxi; Liu, Peitao; Chen, Xing-Qiu; Sun, Yan (Chinese physics letters, 2024)
Topological phonon is a new frontier in the field of topological materials. Different from electronic structures, phonons are bosons and most topological phonons are metallic form. Previous studies about topological phonon states were focused on three-dimensional (3D) materials. Owing to the lack of material candidates, two-dimensional (2D) and van der Waals f -electron-related topological phonons were rarely reported. Based on first-principles calculations, we investigate the topological phononic state in the heavy fermion material CeSiI with a layered structure. Both 3D bulk and 2D monolayers have topological nontrivial states in the rarely seen f electron dominated van der Waals metal. Owing to the PT and C 3 z symmetries, Weyl nodal lines with nonzero Chern numbers exist on the hinge of the Brillouin zone. Protected by C 3 z rotation symmetry, three pairs of Weyl points with ± π Berry phase exist at point K near the frequency of 8 and 10 THz. In addition to the bulk topological charges, corresponding surface/edge states are also systematically analyzed, which gives a consistent understanding. Our results propose another interesting point in the newly discovered rear earth heavy fermion material CeSiI and are helpful for future experimental research of CeSiI topological phonons.